PENGARUH PENGGUNAAN APLIKASI BRAVO, KOMPETENSI PEGAWAI, MOTIVASI PEGAWAI TERHADAP KOPRODUKSI PELAYANAN PUBLIK DI DIREKTORAT LALU LINTAS KEPOLISIAN DAERAH SUMATERA SELATAN - Budi Triharyanto Wibowo; Andries Lionardo; Alamsyah (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
This quantitative explanatory study aims to analyze the influence of the implementation of the BRAVO application, employees’ competence levels, and employee motivation on the effectiveness of co-production in public services at the Traffic Directorate of the South Sumatra Regional Police. The results of the regression analysis reveal that, partially, the variables of employee competence and motivation have a positive and significant influence, while the implementation of the BRAVO application has not yet shown an optimal effect due to limitations in digital capabilities. However, simultaneously, the three independent variables are proven to have a significant influence on the formation of a co-production model, as measured through the indicators of co-assessment, co-design, co-commissioning, and co-delivery. These crucial findings confirm that the success of public service transformation based on co-production requires integral synergy between technological frameworks, high-quality human resource capacity, and sustainable work motivation within a holistic service ecosystem.